Technological challenges and project management in organizations - Spałek, Seweryn (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
Technological challenges have often influenced the development of project management in organizations, and have been the subject of research undertaken by academics from various countries. Particularly nowadays, with the unprecedented acceleration in the dissemination of new technologies, the continuation of research on this topic is becoming ever more important importance. The purpose of the article is to try to answer the question: “Which of the contemporary technologies may poses particular challenges for project management in organizations?”. To obtain the answer, international, empirical, quantitative, questionnaire-based research was conducted. Within the study answers were received from 264 respondents. Analysis of the results allowed the identification of technologies related to Industry 4.0 and social media as currently representing the greatest challenges for project management in organizations.